Antecedents of Consumer Trust in B-to-C Electronic Commerce - KIM, Dan J. (Institutional Knowledge at Singapore Management University, 2003)
Despite the importance of trust in electronic commerce, there is insufficient theory and evidence concerning the determinants of consumer trust about an Internet vendor’s trustworthiness, and the influence of consumer trust on the consumer’s purchasing intention. The purpose of this study is to: i) develop a theoretical framework identifying the antecedents of a consumer’s trust and purchase intention, ii) test the proposed model using Structural Equation Modeling, analyzing Internet consumer behavior data collected via a Web survey, and iii) provide theoretical and managerial implications. The results of the study show that consumers’ disposition to trust, privacy protection, security protection, consumers’ perceptions about the selling party’s reputation, information quality, and system reliability are strong antecedents of consumers’ trust. Interestingly, the presence of a third-party seal did not influence consumers’ trust nor consumers’ purchase intention. Finally, consumer’s trust was a strong predictor of their purchasing intention.